2D Black Phosphorus for Energy Storage and Thermoelectric Applications. Issue 28 (8th June 2017) - Zhang, Yu; Zheng, Yun; Rui, Kun; Hng, Huey Hoon; Hippalgaonkar, Kedar; Xu, Jianwei; Sun, Wenping; Zhu, Jixin; Yan, Qingyu; Huang, Wei
Abstract : Recent progress in the currently available methods of producing black phosphorus bulk and phosphorene are presented. The effective passivation approaches toward improving the air stability of phosphorene are also discussed. Furthermore, the research efforts on the phosphorene and phosphorene‐based materials for potential applications in lithium ion batteries, sodium ion batteries, and thermoelectric devices are summarized and highlighted. Finally, the outlook including challenges and opportunities in these research fields are discussed. Abstract : Phosphorene and phosphorene‐based materials receive extensive attention for potential applications in energy storage and conversion devices. In this Review, the state‐of‐the‐art progress of phosphorene and phosphorene‐based materials for lithium ion batteries, sodium ion batteries, thermoelectric devices, and other energy storage devices are presented.